TRANSLOKASI MERKURI (HG) PADA DAUN TANAMAN BAYAM DURI (AMARANTHUS SPINOSUS L) DARI TANAH TERCEMAR - Irsyad, Muhammad; Sikanna, Rismawaty; Musafira, Musafira (Natural Science: Journal of Science and Technology, 2014)
Research about mercury translocation (Hg) into the leaf of Amaranthus Spinosus L from polluted soil has been carried out. The research aim was to know influences of  remediation time on the abilty of  mercury absorptions , knowing the concentration of mercury distribution in the leaf of A. spinosus L and abilty of A. spinosus L as hyperacumulator plant to the mercury. Remediation times used 14 days, 21 days and  42 days. The consentration of Mercury on the growth medium were 25 ppm, 50 ppm, 75 ppm, and 100 ppm. The result showed  that the time of maximum absorptions were at remediation times of  14 days by mercury acumulation of 70.6901 mg/kg DM (Dry Measure). This value indicated that A. spinosus L. is hyperacumulator to the mercury and it have a potential as phytoremediator on the area that contaminated by mercury.